HYGIENIC ASSESSMENT OF NOISE INDICATORS IN MACHINERY FACILITIES - Xadjayeva U.A. (Modern American Journals, 2025)
Mechanical Engineering The enterprise is characterized by abnormal working conditions that negatively affect the health of its employees and their working conditions. According to the results of the study, in order to improve working conditions, it is recommended to use personal protective equipment for workers, use noise-absorbing devices made of rubber materials, and conduct medical examinations of workers in accordance with Order No. R 200 in order to reduce the intensity of noise and vibrations in the workplace.
Keywords: Mechanical engineering enterprises, noise, frequency, working conditions.